2018
DOI: 10.4081/jlimnol.2018.1794
|View full text |Cite
|
Sign up to set email alerts
|

Do carabids (Coleoptera: Carabidae) and chironomids (Diptera: Chironomidae) exhibit similar diversity and distributional patterns along a spatio-temporal gradient on a glacier foreland?

Abstract: Carabid beetles and chironomid midges are two dominant cold-adapted taxa, respectively on glacier forefiel terrains and in glacialstream rivers. Although their sensitivity to high altitude climate warming is well known, no studies compare the species assemblages exhibited in glacial systems. Our study compares diversity and distributional patterns of carabids and chironomids in the foreland of the receding Amola glacier in central-eastern Italian Alps. Carabids were sampled by pitfall traps; chironomids by kic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…As documented for other stream ecosystems in the Alps (Lods-Crozet et al, 2001;Lencioni & Gobbi, 2018;Scotti et al, 2019), kryal sites were dominated by chironomids, representing up to 100 % of the macroinvertebrate fauna at two sites (AG1 and CR0). However, the percentage of chironomids decreased with decreasing glacial influence, and with increasing channel stability, water temperature, and food availability (e.g.…”
Section: Discussionmentioning
confidence: 53%
See 1 more Smart Citation
“…As documented for other stream ecosystems in the Alps (Lods-Crozet et al, 2001;Lencioni & Gobbi, 2018;Scotti et al, 2019), kryal sites were dominated by chironomids, representing up to 100 % of the macroinvertebrate fauna at two sites (AG1 and CR0). However, the percentage of chironomids decreased with decreasing glacial influence, and with increasing channel stability, water temperature, and food availability (e.g.…”
Section: Discussionmentioning
confidence: 53%
“…The quantitative faunal data, expressed as total invertebrate density (ind/m 2 ) per sample (site × season), were [log (x+1)] transformed prior to classification and ordination analyses for normalisation. A cluster analysis (paired group -UPGMA), based on the Bray-Curtis similarity coefficient, was performed to highlight similarities among sites in relation to the macroinvertebrate community (Sneath & Sokal, 1973;Lencioni et al, 2018). Furthermore, a distance-based redundancy analysis db(RDA) was performed to investigate the relationships between fauna and environmental conditions.…”
Section: Discussionmentioning
confidence: 99%
“…two papers addressed the focal issue of climate and environmental changes. the effects of global warming and glacier retreating were evaluated by Lencioni and Gobbi (2018) in a glacier foreland in the italian alps. they demonstrated that increasing glacial retreat differently affect epigeic and aquatic insect taxa: carabid beetles respond faster to glacier retreat than do chironomids, at least in patterns of species richness and species turnover.…”
Section: Special Issue Contentsmentioning
confidence: 99%